2008
DOI: 10.3748/wjg.14.876
|View full text |Cite
|
Sign up to set email alerts
|

Berberine reverses free-fatty-acid-induced insulin resistance in 3T3-L1 adipocytes through targeting IKKβ

Abstract: AIM:To i n v e s t i g a t e t h e e f f e c t s a n d m o l e c u l a r mechanisms of berberine on improving insulin resistance induced by free fatty acids (FFAs) in 3T3-L1 adipocytes. METHODS:The model of insulin resistance in 3T3-L1 adipocytes was established by adding palmic acid ( 0 . 5 m m o l / L ) t o t h e c u l t u re m e d i u m . B e r b e r in e treatment was performed at the same time. Glucose uptake rate was determined by the 2-deoxy-[3 H]-Dglucose method. The levels of IkB kinase beta (IKKβ) Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 28 publications
2
32
1
Order By: Relevance
“…The antiinflammation activity of KPF has been reported in vitro and in vivo by other studies [14,36], and our work also confirmed its antiinflammatory effect in T2DM. High-dose of salicylate is a potent inhibitor of inflammation, which prevents insulin resistance by inhibiting IKKβ activation, and our results were in accordance with those reports by Sun et al [18,37].…”
Section: Discussionsupporting
confidence: 96%
“…The antiinflammation activity of KPF has been reported in vitro and in vivo by other studies [14,36], and our work also confirmed its antiinflammatory effect in T2DM. High-dose of salicylate is a potent inhibitor of inflammation, which prevents insulin resistance by inhibiting IKKβ activation, and our results were in accordance with those reports by Sun et al [18,37].…”
Section: Discussionsupporting
confidence: 96%
“…by the activation of the two serine/threonine kinases, which have been previously demonstrated to be activated by the proinflammatory conditions associated with insulin resistance (26,83,84). The involvement of IKKb and JNK in our experimental model was in agreement with several published papers, which have suggested serine kinases activation as an intervening mechanism in inducing insulin resistance (25,(30)(31)(32)(33)(34)(85)(86)(87).…”
Section: Oxldl Impair Insulin Signaling In Adipocytes 839supporting
confidence: 80%
“…29,30 In the 3T3-L1 adipocytes model of insulin resistance, berberine reverses 1κB kinase beta Ser(181) and insulin receptor substrate-1 (IRS-1) Ser(307) phosphorylation, improves insulin-stimulated glucose transport, and reverses free fatty acid-induced insulin resistance (palmitic acid in this study). 31 Berberine seems to improve insulin resistance by upregulating IRS-2 mRNA expression in nonalcoholic fatty liver disease in the rat liver. 32 However, in another study, which was conducted on 3T3-L1 adipocytes, berberine did not augment IRS-1 or insulin receptor tyrosine phosphorylation.…”
Section: Effects Of Berberine On Insulin Resistance and Fatty Acid Mementioning
confidence: 99%